Meningkatkan Ekonomi Kreatif melalui Pelatihan Pengolahan Singkong pada Masyarakat Desa Sumur - Latifah Alkhoiriyah; Hilda Hildayati; Andini Purna Dita; Dewi Harnisa Pangesti; Muslimatul Ibadah; Nurma Kurnia Putri; Rosalia Ramawati (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
The processing of garden products, namely cassava as an effort to develop the community's economy and increase the creative economy of the Sumur Village community is one of the leading work programs of post 94 in completing the community service process. This community service activity is a form of training for the community in the implementation of cassava garden product processing in Sumur Village, Brangsong District, Kendal Regency. The factor that encouraged group 94 to process garden products in Sumur Village was the abundance of cassava plants that were not optimally utilized. So it needs to be optimized as a food ingredient that is ripe and ready to be. The implementation of the community service above also has a mission to create new innovations in the processing of garden products, namely cassava can be processed into cassava rengginang, cassava layer, cassava brownies, cassava dodol, mocaf flour, and cheese cendol (cheese cassava). The implementation of this community service uses a training method for the community whose majority livelihood is as a farmer. The stages carried out are starting preparations, namely recording data on residents who work as farmers and the availability of cassava harvests on the Plantation. Next, start the implementation stage by involving extension workers from the Kendal Regency UMKM Service to help provide processing training on the potential of cassava harvests from raw to cooked. This service aims to improve the creative economy through cassava processing training for the people of Sumur Village.